P622 Staphylococcic necrotizing pneumonia in a two months infant. (June 2019) - Charfi, Manel; Hamad, Amel Ben; Abdelkrim, Rim; Regaieg, Chiraz; Bouraoui, Amira; Regaieg, Ridha; Hmida, Nedia; Thabet, Afef Ben; Gargouri, abdellatif
Abstract : Introduction: Acute necrotizing pneumonia associated to Panton-Valentine Leukodine (PVL) producing staphylococcus aureus is a recent clinical entity identified by Gilet and all in 2002. It's a life threatening condition that can lead to rapid death despite a rapid management. It's rarely described on young infants less than one year old. Methods: We report the case of a two months old infant who was admitted in our unit for acute necrotizing pneumonia associated to PVL producing and Methicillin resistant Staphylococcus aureus. Results: A two months old boy with no past medical history was admitted in our unit for acute fever. His mother was nurse in our unit and his father was a nurse in the intensive care unit. Physical exam on admission showed high fever with tachycardia and acrocyanosis. Blood count was normal. The C reactive protein level was of 13mg/l. Chest radiography showed an infiltrate of the right lobe. Empiric antibiotic therapy with cefotaxim and vancomycin was started. Six hours after admission the infant developed cyanosis an acute dyspnea. Control chest radiography showed a huge pneumothorax. Mechanic ventilation was then started and a chest tube was set up. Drainage of the pleural cavity brought a purulent fluid. Bacteriological examination of the pleural fluid revealed a methicillin-resistant and a PVL producing Staphylococcus aureus. The same germ was found in the nasopharyngeal swab of the two parents as well as the infant claiming then an intrafamilial transmission. Clindamycin was added to the initial antibiotic therapy. Follow up chest radiography showed pneumatocele. The evolution was favorable. Chest tube was removed after 5 days. The infant was extubated a day after and he was dischaged after 4 weeks of triple antibioticc therapy. He is now 9 months old. His physical exam is normal as well as his chest radiography. Conclusion: The diagnosis of staphylococcic necrotizing pneumonia must be kept in mind every time one of these following signs is associated: viral infection preceding the onset, hemoptisis, rapid worsening, multilocular infiltrates, pneumatocele, pleural effusion or leucopenia. Moreover an association of anti-staphylococcal and anti-toxin antibiotic must be started even before bacteriological confirmation.